Validation Paud teacher Competency Design for the Autism Foundation X - Wiriana, Dinda Ferani; Wiriana; Widarnanda, I Gde Dhika (LPPM Universitas Dhyana Pura, 2025)
This study aims to validate Kurnia's (2019) PAUD teacher competency design, which will be suggested to be applied at Foundation X. This research was compiled because at Foundation X there is no teacher competency table that can be used as a reference in human resource management and provide briefings to teachers related to learning students with disabilities. The descriptive method is used in the research, as well as an internal validity test. The test involved a scale assessment and interviews with three experts and three practitioners. The study's results demonstrate the validity of the teacher competency table, as the average value of experts and practitioners exceeds the criterion of 87.09 > 75, indicating that the table is suitable for testing and application.